Predictors of outcome in heart failure patients with severe functional mitral regurgitation undergoing MitraClip treatment. (1st June 2019) - Baldi, Cesare; Citro, Rodolfo; Silverio, Angelo; Di Maio, Marco; De Rosa, Roberta; Bonadies, Domenico; Verolino, Giuseppe; Esposito, Luca; Mastrogiovanni, Generoso; Di Muro, Michele Roberto; Piscione, Federico; Galasso, Gennaro
Abstract: Background: The prognostic predictors of outcome in patients with functional mitral regurgitation (FMR) undergoing MitraClip implantation (MCi) are still poorly known. The aim of our study is to identify the baseline predictors of outcome in FMR patients candidate to MCi. Methods: All patients with symptomatic moderate-to-severe or severe FMR undergoing MCi at our institution were consecutively and prospectively enrolled. Baseline clinical and instrumental data were collected. Primary endpoint was the occurrence of cardiac death; secondary endpoints were all-cause death and the composite of cardiac death or rehospitalization for heart failure. Results: 74 patients (mean 71.6 ± 8.3 years) were enrolled. During follow-up (median 416.0 days), the primary endpoint occurred in 15 (20.3%), all-cause death in 26 (35.1%) and the composite endpoint in 25 (33.8%). At multivariate analysis, the left atrial volume index (LAVi; HR:1.02; P  = 0.048) and the low peak oxygen uptake (peak VO2 ; HR:0.73; P  = 0.018) increased the risk of cardiac death at follow-up; atrial fibrillation (AF; HR:2.69; P  = 0.027) was independently associated to all-cause death and the low level of peak VO2 was an independent predictor of overall mortality (HR:0.70; P  < 0.001) as well as of the composite endpoint (HR:0.73; P  < 0.001). The ROC analysis identified a peak VO2 cut-off of 10.0 mL/kg/min as the best predictor for the three study endpoints; the best LAVi cut-off for cardiac death was 67 mL/m 2 . Kaplan-Meier analysis for the individual and combined outcome predictors confirmed their significant stratification ability during follow-up. Conclusions: Peak VO2, along with LAVi and AF, identify FMR patients with the worst prognosis after MCi. Highlights: The MCi eligibility of FMR patients needs a multiparametric evaluation to avoid futility. Baseline peak VO2, LAVi and AF are independent predictors of events after MCi. In FMR patients peak VO2  < 10 mL/kg/min carried the worst prognosis after MCi.